2022
DOI: 10.1103/physreva.105.012430
|View full text |Cite
|
Sign up to set email alerts
|

Landauer's principle in qubit-cavity quantum-field-theory interaction in vacuum and thermal states

Abstract: We consider quantum decoherence and Landauer's principle in qubit-cavity quantum field theory (QFT) interaction, treating the qubit as the system and cavity QFT as the environment. In particular, we investigate the changes that occur in the system with a pure initial state and environment during the decoherence process, with or without energy dissipation, and compare the results with the case in which the initial state of the system is a mixed state and thus decoherence is absent. When we choose an interaction… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(21 citation statements)
references
References 55 publications
(28 reference statements)
0
11
0
Order By: Relevance
“…When the initial state of the Dirac field is a thermal state, we obtained the heat transfer and entropy grow approximately under some additional conditions and also verified the validity of the Landauer's principle. We find that compared to the case of real scalar field [20], the results of vacuum initial state differs only due to the helicity of the Dirac field while for thermal initial state, the distinguishability of fermion and anti-fermion also plays its part. Our work holds the potential of being extended to the QCD systems and neucleaon-neutrino systems [26,27,28], which may be experimental feasible.…”
Section: Discussionmentioning
confidence: 79%
See 3 more Smart Citations
“…When the initial state of the Dirac field is a thermal state, we obtained the heat transfer and entropy grow approximately under some additional conditions and also verified the validity of the Landauer's principle. We find that compared to the case of real scalar field [20], the results of vacuum initial state differs only due to the helicity of the Dirac field while for thermal initial state, the distinguishability of fermion and anti-fermion also plays its part. Our work holds the potential of being extended to the QCD systems and neucleaon-neutrino systems [26,27,28], which may be experimental feasible.…”
Section: Discussionmentioning
confidence: 79%
“…Taking TR → 0, the results reduce to (15) under resonance approximation. Substitute (20) into (21) it is easy to check that the Landauer's principle ∆Q ≥ TR∆S is satisfied. The initial state of the detector can also be assigned with a temperature TD with p = e .…”
Section: Thermal Statementioning
confidence: 99%
See 2 more Smart Citations
“…Recently it was found that the decoherence rate can be used to measure the Unruh effect [38]. We can also study the exchange of energy and information during the interaction between the detector and quantum field theory [39][40][41], which may help us to understand the feedback and back-reaction obtained from the measurements, as well as the connection between gravity and quantum theory. In [40] we also investigated the decoherence of the qubit coupled to a thermal quantum field theory in a cavity, and the results are also consistent with our Theorem 1.…”
Section: From D To D +mentioning
confidence: 99%